EXPERT SYSTEM FOR EARLY DETECTION OF BREAST CANCER WITH THE FORWARD CHAINING METHOD - Caniago, Diana; Andryana, Septi; Gunaryati, Aris (Journal of Intelligent Decision Support System (IDSS), 2020)
Breast cancer will be easier to overcome if it is known as early as possible to the importance of self-awareness to perform a routine inspection of BSE. The study presented aims to design a web-based application in the health field in the early detection of breast cancer. Penelian expert system method on this is to use forward chaining to represents the rule and reasoning into a coherent system based on physical symptoms entered. In this system also gets a percentage probability of 72.7%, so it can be quite good. In addition the system can produce two outputs in the form of possibility, the output is both benign and malignant.